Corvalán for Bukovsky: A Real Exchange of Prisoners During an Imaginary War. the Chilean Dictatorship, the Soviet Union, and Us Mediation, 1973-1976 - Ulianova, O (Routledge, 2014)
Based on Chilean, Soviet, American, and Italian declassified documents, this article examines a particular case in the global Cold War: the only international exchange of political prisoners during that period, involving the general secretary of the Chilean Communist Party Luis Corvalán and Soviet dissident Vladimir Bukovsky. It emphasises the intersecting agendas, purposes, and consequences of multiple state and non-state actors in this episode: from the governments of Chile, the US, and the USSR, to the Chilean Communist Party, the Soviet dissident movement, and finally to the European communist parties, Cuba, international solidarity, and human rights movements. © 2013 Taylor and Francis.